2016
DOI: 10.4172/2155-6156.1000705
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Prevalence among Prediabetic and Normoglucotolerant Women

Abstract: Prediabetes is a known risk factor for type 2 diabetes and lead to long term complications such as cardiovascular diseases. In Cameroon, they are limited data dealing with prediabetes prevalence among Cameroonians. Our study objective was to estimate the prevalence of metabolic syndrome among prediabetic women and normoglyceamic women. Methods:A total of 200 women (100 prediabetic women and 100 normoglyceamic) participated in the study, they were aged between 20-55 years. For their studied data, they were refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…When the prevalence of MetS was considered among prediabetic patients, the prevalence was higher than MetS alone or prediabetes alone among the population studied. This can be expected because the component of MetS is more obvious in prediabetic state [20].…”
Section: Discussionmentioning
confidence: 90%
“…When the prevalence of MetS was considered among prediabetic patients, the prevalence was higher than MetS alone or prediabetes alone among the population studied. This can be expected because the component of MetS is more obvious in prediabetic state [20].…”
Section: Discussionmentioning
confidence: 90%
“…Overall, 40% of the samples had hypertension in pre-diabetes patients. Mandob and Sabine reported that 59% of pre-diabetic patients suffer from hypertension [23].…”
Section: Discussionmentioning
confidence: 99%